Efficacy and safety of inhaled low-dose methoxyflurane for acute paediatric pain: A systematic review. (April 2019) - Hartshorn, Stuart; Middleton, Paul M
Introduction: Undertreatment of acute, moderate-to-severe pain in children is common, due in part to barriers to the use of opioids. Low-dose methoxyflurane is an inhaled, non-opioid analgesic widely used in Australia and recently approved in Europe for the emergency relief of acute moderate-to-severe trauma pain in adults. Methods: Using an integrative review framework, we conducted a literature analysis to examine the potential utility of methoxyflurane in children with acute pain. EMBASE®, MEDLINE® and PubMed were searched (criteria included 'methoxyflurane' 'child*' or 'adolescent' or 'pediatr*' or 'paediatr*') from January 2000 to October 2017, along with internet-based sources to identify relevant grey literature (no predefined search criteria). A series of investigative questions were developed regarding the safety and efficacy of methoxyflurane in this setting and addressed using evidence collated from the identified studies. Results: Of 366 results from the literature searches, 6 clinical trials and observational studies were identified which explored the safety and/or efficacy of inhaled methoxyflurane in individuals < 18 years in either a clinical trial or observational study. All six studies concluded that methoxyflurane provides effective and rapid analgesia for paediatric acute moderate-to-severe pain. Methoxyflurane was well tolerated and associated with good levels of patient/healthcare provider satisfaction in this setting. Conclusions: While large-scale studies are needed to better inform treatment approaches for paediatric use, inhaled methoxyflurane has potential to provide easy to administer, needle-free analgesia with a rapid onset and good safety profile.